The subunit vaccine H65 + CAF01 increased the BCG- protection against Mycobacterium bovis infection in a mouse model of bovine tuberculosis - Blanco, Federico Carlos (2021)
H65, a fusion protein of three pairs of ESX-secreted antigens of Mycobacterium tuberculosis and Mycobacterium bovis, formulated with the liposomal adjuvant CAF01 has been shown to confer protection against M. tuberculosis infection in mice. In this study, we evaluated the impact of combining BCG with H65 + CAF01 immunization in a M. bovis mouse model of infection. We found that a BCG-H65 + CAF01/ H65 + CAF01 prime-boost scheme induced higher protection than BCG and H65 + CAF01 alone. Altogether, H65 antigen formulated in liposomal adjuvant improved the BCG-induced immune protection, thus making this vaccine strategy a promising tool to control bovine tuberculosis.